Innovations in Therapeutic Improvement of the Cutaneous Microbiome in Children with Atopic Dermatitis - Nikolay N. Murashkin; Roman V. Epishev; Roman A. Ivanov; Alexander I. Materikin; Leonid A. Opryatin; Alena A. Savelova; Roza Y. Nezhvedilova; Roza T. Ambarchian; Dmitri V. Fedorov; Lyudmila L. Rusakova ("Paediatrician" Publishers LLC, 2022)
Biofilm is the dominant form of skin microbiota organization that provides adhesion and preservation of microorganisms in the skin micro-environment. It is necessary to ensure epidermal barrier function and local immunomodulation. Staphylococcus aureus becomes the major colonizer of skin lesions in case of atopic dermatitis exacerbation, and it also can form the biofilms. S. aureus growth and biofilm formation due to other microbial commensals on the skin of patients with atopic dermatitis leads to chronic output of pro-inflammatory cytokines and later to abnormalities in healthy skin microbiome. The role of microbial biofilm in human's health makes the skin microbiota an attractive target for therapeutic intervention in various skin diseases.